Temporal dynamics of total and active root-associated diazotrophic communities in field-grown rice - Luo, Xue; Ye, Xianfeng; Wang, Wenhui; Chen, Yang; Li, Zhoukun; Wang, Yanxin; Huang, Yan; Ran, Wei; Cao, Hui; Cui, Zhongli (Frontiers in Microbiology, 2022)
Plant-associated nitrogen-fixing microorganisms (diazotrophs) are essential to host nutrient acquisition, productivity and health, but how host growth affects the succession characteristics of crop diazotrophic communities is still poorly understood. Here, Illumina sequencing of DNA- and RNA-derived nifH genes was employed to investigate the dynamics of total and active diazotrophic communities across rhizosphere soil and rice roots under four fertilization regimes during three growth periods (tillering, heading and mature stages) of rice in 2015 and 2016. Our results indicated that 71.9-77.2% of the operational taxonomic units (OTUs) were both detected at the DNA and RNA levels. According to the nonmetric multidimensional scaling (NMDS) ordinations of Bray‒Curtis distances, the variations in community composition of active rhizosphere diazotrophs were greater than those of total rhizosphere diazotrophs. The community composition (β-diversity) of total and active root-associated diazotrophs was shaped predominantly by microhabitat (niche) (R2 ≥ 0.959, P < 0.001), followed by growth period (R2 ≥ 0.15, P < 0.001). The growth period had a stronger effect on endophytic diazotrophs than on rhizosphere diazotrophs. From the tillering stage to the heading stage, the α-diversity indices (Chao1, Shannon and phylogenetic diversity) and network topological parameters (edge numbers, average clustering coefficient and average degree values) of total endophytic diazotrophic communities increased. The proportions of OTUs shared by the total rhizosphere and endophytic diazotrophs in rhizosphere diazotrophs gradually increased during rice growth. Moreover, total diazotrophic α-diversity and network complexity decreased from rhizosphere soil to roots. Collectively, compared with total diazotrophic communities, active diazotrophic communities were better indicators of biological response to environmental changes. The host microhabitat profoundly drove the temporal dynamics of total and active root-associated diazotrophic communities, followed by the plant growth period.